Information Systems for Monitoring the Burden of Chronic Diseases in Public Reference Health Facilities in Central Africa - Verbeke, Frank; Hategekimana, Théobald; Karara, Gustave; Ly, Ousmane; Nimburanira, Marc; Kayembe, Charles; Nyssen, Marc (Journal of Health Informatics in Africa, 2013)
Background and purpose: Chronic diseases are an increasingly important cause of death in sub-Saharan Africa. Diseases such as cancer, diabetes and arterial hypertension remained for years in the background, in the shadow of pandemics such as malaria, HIV / AIDS and tuberculosis. Chronic disease incidence in the Central African region however, is poorly documented. This study explores to what extent secondary use of clinical information stored in hospital information systems can help to provide evidence related to the burden of diabetes, cancer and hypertension in DR Congo, Rwanda and Burundi. Methods: In the past 6 years, 4 reference hospitals of Kisangani, Bukavu, Kigali and Bujumbura implemented open source hospital information management tools integrating international classification systems such as ICD-10 and ICPC-2. Clinical and financial data from chronic disease treatments in the period 2006-2012 were merged into Diagnosis Related Groups (DRGs) for further analysis. Metrics related to case load, mortality load and financial burden have been calculated for diabetes, cancer and hypertension DRGs. Results: 89,765 out-patient visits and 59,434 admissions have been analyzed in this study. The results show a worrying growth of the 3 chronic diseases in the region. Costs related to the studied diseases are expected to increase by 10% (diabetes) to 70% (cancer & hypertension) between 2011 and 2015 in the studied reference hospitals. Conclusion: the study demonstrates that the problem of chronic diseases also grows rapidly in the Great Lakes region and therefore urgent steps must be taken, both by governments (Rwanda, DRC and Burundi), by the international donor community and by local hospital boards. Keywords :Information systems, Diagnosis-Related Groups, Chronic Disease, Sub-Saharan Africa, Neoplasms, Hypertension, Diabetes